2019
DOI: 10.15640/jcsit.v7n2a4
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Blockchain Technology Adoption

Abstract: Governments of emerging economies need to stimulate awareness and adoption of emerging technologies to facilitate effective and efficient citizen service delivery. The need for an integrated Information Communication Technology ecosystem in developing countries, nurture the call for adoption of emerging technologies. Similar to every emerging technology, the adoption of blockchain is dependent on the extent that government and relevant stakeholders take the lead in supporting and unveiling market-creating inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
1
3
1
Order By: Relevance
“…This result agrees with the findings of Nmor (2015) and Ocheje and Dogara (2016), who obtained similar results in southern Nigeria and Jigawa, respectively. The result is, however, different from the findings of Dawaki et al (2016) and Jimoh et al (2019) who reported that the effect on children below five years is significantly different from that of pregnant women in Kano and Kaduna States, respectively. The result is also at variance with the findings of Bajoga et al (2019) and Awosolu et al (2021) who reported that children are more affected than pregnant women in Kaduna State and Ibadan, in Oyo State, respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result agrees with the findings of Nmor (2015) and Ocheje and Dogara (2016), who obtained similar results in southern Nigeria and Jigawa, respectively. The result is, however, different from the findings of Dawaki et al (2016) and Jimoh et al (2019) who reported that the effect on children below five years is significantly different from that of pregnant women in Kano and Kaduna States, respectively. The result is also at variance with the findings of Bajoga et al (2019) and Awosolu et al (2021) who reported that children are more affected than pregnant women in Kaduna State and Ibadan, in Oyo State, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…A Tukey posthoc test showed that the prevalence of malaria at Dutsen Abba is significantly different from Kaura, Dambo, Ungwar Fatika, Tukur-Tukur, Kwabai B, Ungwar Juma and Wuciciri. These results corroborate the findings of Jimoh et al (2019) who showed significant differences in the prevalence of malaria by hospital locations in Kaduna State. The result, however, disagrees with the findings of Awosolu et al (2021), who reported lower cases of malaria in urban areas.…”
Section: Discussionsupporting
confidence: 91%
“…Also, infrastructural development through the built environment sector is key to enhancing the economy. However, there are few studies on blockchain in Nigeria's context, such as Abodei et al (2019), Ajao et al (2019), Jimoh et al (2019) and Akaba et al (2020). These studies did not address the blockchain concept concerning the built environment sector.…”
Section: Introductionmentioning
confidence: 99%
“…We used multiple regression estimates to test the hypothesis due to the limited number of data sets (Eckstein et al, 2015). However, the result is novel and contributes to blockchain and corporate governance literature as studies examined were mainly theoretical (Akaba, 2019;Jimoh et al, 2019;Oye-Bamgbose, 2019). Moreover, R 2 coefficients show that the model was able to explain 52% of the variance in corporate governance.…”
Section: Resultsmentioning
confidence: 93%